Trends in the Occurrence of Parvoviral Enteritis in Local Canine Population: A Trohoc Study - Subramanian, Saravanan; Thangamani, Arulkumar; Ganapathy, Selvaraju (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Parvoviral enteritis (PVE) in dogs causes haemorrhagic diarrhoea, vomiting and leukopenia resulting in sepsis and death. Though the  disease is more commonly reported in young dogs, adult dogs of pure breeds are also vulnerable to PVE, due to the breakdown of  immunity. Hence, a retrospective study on the occurrence of PVE in dog population of local region of Namakkal, Tamil Nadu (India)  over two years was conducted. The incidence rate in the year 2023 and 2024 was high in dogs with the age group of 0-3 months (39.7%  and 37.3%), males (77.9 and 70.7 %) and non-descript breeds (62.3 and 64.7 %). A high incidence was observed in summer (32.5 %)  in the year 2023 and south-west monsoon (59.2 %) in 2024. Between the two years, a significant difference (p
Keywords: Canine parvo virus-2; Haemorrhagic diarrhoea; Host factors; Retrospective study